2015
DOI: 10.1016/j.cognition.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for the role of shared space in online comprehension of spatial demonstratives

Abstract: a b s t r a c tA fundamental property of language is that it can be used to refer to entities in the extralinguistic physical context of a conversation in order to establish a joint focus of attention on a referent. Typological and psycholinguistic work across a wide range of languages has put forward at least two different theoretical views on demonstrative reference. Here we contrasted and tested these two accounts by investigating the electrophysiological brain activity underlying the construction of indexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 37 publications
(73 reference statements)
4
36
1
1
Order By: Relevance
“…Here, we show that those trajectory modifications increase the informational value of the pointing movement, when seen from the spatial perspective of the addressee, which was not yet implied by the previous observations on this data set (Murillo Oosterwijk et al., ). This observation lends itself to be interpreted in terms of recipient design, in line with previous observations suggesting that communicators organize their movement in an inferential perspective centered on the addressee (Blokpoel et al., ; Heller, Grodner, & Tanenhaus, ; Peeters, Hagoort, & Özyürek, ; Surtees, Apperly, & Samson, ). By the same token, the current findings are not immediately compatible with accounts that consider recipient design exclusively as a communicative repair operation (Horton & Keysar, ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Here, we show that those trajectory modifications increase the informational value of the pointing movement, when seen from the spatial perspective of the addressee, which was not yet implied by the previous observations on this data set (Murillo Oosterwijk et al., ). This observation lends itself to be interpreted in terms of recipient design, in line with previous observations suggesting that communicators organize their movement in an inferential perspective centered on the addressee (Blokpoel et al., ; Heller, Grodner, & Tanenhaus, ; Peeters, Hagoort, & Özyürek, ; Surtees, Apperly, & Samson, ). By the same token, the current findings are not immediately compatible with accounts that consider recipient design exclusively as a communicative repair operation (Horton & Keysar, ).…”
Section: Discussionsupporting
confidence: 86%
“…This study adds to previous work on communicative pointing by quantifying the informative value of those movements. For instance, it is known that communicative pointing results in more emphatic pointing stroke duration (Peeters, Hagoort, & Ozyurek, ) and longer holding times than those evoked in control conditions (Murillo Oosterwijk et al., ). Furthermore, the trajectories of communicative pointing movements are influenced by the spatial location of the addressee (Murillo Oosterwijk et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, recent experimental work makes clear that space cannot be the sole basis of demonstrative variation. An interesting recent study in this respect is Peeters, Hagoort and Özyürek (2015), which suggests that interlocutors construe a shared space during conversation, whereby psychological proximity of a referent may be more important than its physical proximity.…”
mentioning
confidence: 98%
“…Similarly, in half of the saliency pictures the object at her left was framed and in the other half the object at her right. The 40 different table-top objects in the pictures were selected on the basis of a pre-test reported elsewhere (Peeters et al, 2015b) that confirmed that these objects elicited highly consistent labels (i.e. > 90% naming consistency for each object across 16 participants) across individuals from the same participant pool as the current participants.…”
Section: Stimulus Materials and Experimental Designmentioning
confidence: 99%
“…Pointing gestures may single out an object from a larger set of potential referents while speech may concomitantly describe the object (Bühler, 1934;Clark and Bangerter, 2004), as in someone pointing at an apple while saying "I have bought this apple at the market this morning" (Peeters et al, 2015b). Previous work suggests that conceptual matching between auditory and visual information may recruit pMTG (e.g., Dick et al, 2014).…”
Section: Introductionmentioning
confidence: 99%